2020
DOI: 10.1007/s00101-020-00885-5
|View full text |Cite
|
Sign up to set email alerts
|

Notfallmedizin in der Deutschen Gesellschaft zur Rettung Schiffbrüchiger – Auswertung medizinischer Notfälle auf der Nord- und Ostsee über 2 Jahre

Abstract: Zusammenfassung Hintergrund Die logistischen Besonderheiten eines maritimen Notfallortes und die häufig zusätzlich drohende akzidentelle Hypothermie machen die Versorgung medizinischer Notfälle auf dem Meer besonders anspruchsvoll. In dieser Arbeit sollen die Charakteristika notfallmedizinischer Einsätze der Deutschen Gesellschaft zur Rettung Schiffbrüchiger (DGzRS) als Hauptträgerin der nichthelikopterbasierten medizinischen Seenotrettung auf den Meeren vor der deutschen Küste beschrieben werden. Material un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Few studies have reported about medical operations by lifeboat crews at sea. Studies on this subject endorse that these operations are diverse, demanding and complicated, caused by the combination of limited resources, large distance from land and medical facilities, and often serious medical problems [ 2 , 3 , 6 , 7 ]. The studies also report a wide variety of medical problems, from small wounds to death, resembling the findings in this study [ 2 , 3 , 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have reported about medical operations by lifeboat crews at sea. Studies on this subject endorse that these operations are diverse, demanding and complicated, caused by the combination of limited resources, large distance from land and medical facilities, and often serious medical problems [ 2 , 3 , 6 , 7 ]. The studies also report a wide variety of medical problems, from small wounds to death, resembling the findings in this study [ 2 , 3 , 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study from Hawaii reports significant improvement in patient outcome after ambulance crew co-responded to emergencies at sea [ 4 ]. A German study demonstrated a higher severity of disease in maritime rescue compared to emergency medical services in a nearby town, recommending more professional support on board, for instance by an emergency physician [ 2 ]. One of the observations in this German study was the delay of departure (average of 18 min longer), due to the waiting time for arrival of the physician at the rescue station.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dykes et al found that approximately 19% of all search-and-rescue missions in the maritime environment included the need for at-sea medevacs, and Peake et al demonstrated that the average cruise ship's physician could expect to see a life-threatening illness or injury four times per voyage with at least one requiring urgent transportation ashore [5,6]. Schemke et al analyze the operations of search-and-rescue providers, utilizing triage severity scores to demonstrate that the disease and injury acuity for maritime missions were much higher than those reported in an average city's land-based emergency medical services [7].…”
Section: Introductionmentioning
confidence: 99%